Synthesis, in Vitro and in Silico Biological Studies of Sulfonamide Chalcones as Esterase Inhibitors - Arslan, Tayfun; Senturk, Murat; Karagoz, Lutfi; Karagoz, Yalcin; Ekinci, Deniz; Efe, Asiye; Uras, Fikriye (Wiley-VCH Verlag GmbH, 2022)
Inhibition profiles of synthesized 4-methyl benzene sulfonamide derivatives on carbonic anhydrase I (CA I) and II (CA II), acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) were investigated in this study. All sulfonamide based compounds showed the inhibition profiles with K-I values in the range 0.39-2.46 nM for CA I, 4.81-14.43 nM for CA II, 52.10-58.83 nM AChE and 50.78-57.38 nM for BChE, respectively. CA Isoenzymes are essential therapeutic targets and their inhibitors have been used for pharmacological purposes particularly in the remedy of diseases such as glaucoma, edema, cancer, etc. Cholinesterase inhibitors are important compounds that can be used in many diverse therapeutic applications, especially Alzheimer's disease (AD). The 4-methyl benzene sulfonamides examined here and acetazolamide, the clinically used CA Inhibitor, showed similar results for CA I and II. Similarly, synthesized compounds demonstrated close inhibition ranges with neostigmine, a cholinesterase inhibitor, on AChE and BChE enzymes. These results indicate that these molecules can be used as potential inhibitors for these esterase enzymes. In addition, molecular docking studies were carried out to elucidate the mechanism of the observed activities of the potent compounds.
Karagöz, Yalçın/0000-0002-4835-4508; Türkoğlu, Emir Alper/0000-0001-7850-6456; Senturk, Murat/0000-0002-9638-2896
Keywords: Carbonic Anhydrase; Chalcone; Cholinesterase; Enzyme Inhibitor; Sulfonamide